2020
DOI: 10.35691/jbm.0202.0157
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Damage Assessment of Snail in Cultivated Crops of Neelabut Bagh Azad Jammu And Kashmir (Pakistan)

Abstract: The present study was conducted to study diversity and damage assessment of snails in cultivated crops and ornamental plants. The study revealed two types of snail species Macrochlamys indica and Indoplanorbis exustus in the study area. The sampled plots of tomato, Karam, Palak, Dhania, Maize, Fresh beans, Sunflowers, Aloe Vera, Loki, Pumpkin, Bitter guard, Kheera, Kachmach, Hund were taken. The study revealed that at Neelabut, when 39 plants of Fresh beans were examined out of them 18 were found damaged and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This Indo-Asian ariophantid snail is native to Bangladesh, India, and Nepal [13,18,22,[37][38][39][40]. It is proposed to be introduced to the Andaman Islands and Sri Lanka [16,39], Pakistan [41], Peninsular Malaysia [42], and Sabah and adjacent islands [43]. Recently, Agudo-Padrón and Luz [44] and Kudo et al [19] reported the occurrence M. indica as an alien species in southern Brazil and Japan, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This Indo-Asian ariophantid snail is native to Bangladesh, India, and Nepal [13,18,22,[37][38][39][40]. It is proposed to be introduced to the Andaman Islands and Sri Lanka [16,39], Pakistan [41], Peninsular Malaysia [42], and Sabah and adjacent islands [43]. Recently, Agudo-Padrón and Luz [44] and Kudo et al [19] reported the occurrence M. indica as an alien species in southern Brazil and Japan, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This snail is commonly found attached to aquatic plants in small ponds, pools, lakes, and rice paddy fields, including in semi-permanent pool flooding fields. I. exustus acts as an important plant pest because it reduces the vigor of some crops by killing seeds or seedlings, destroying stems or growing points, or causing leaf damage, which subsequently causes economic loss [11,12].…”
Section: Introductionmentioning
confidence: 99%